The constitution of the subject according to Jean-Paul Sartre - da Silva, Lúcia Cecília; Vaccaro, Marina Menegueti (Revista de Psicologia, 2017)
The issues on the subject, on the human being, widely concern mankind and several areas of knowledge. Understanding the subject and the processes by which such a subject is constituted is the central focus and basis of psychological science. However, this object of study has difficulties, which are evident in the different approaches to it, either objectivist or subjectivist ones. In order to contribute to such discussion, this study aims at analyzing how the existentialism of Jean-Paul Sartre approaches the processes of the constitution of the subject. The Sartrean perspective enriches Psychology because, by rejecting reductionisms, it offers a conception that does not dichotomize the phenomenon of objectification-subjectification, since it conceives the subject in the dialectical relation between objectivity and subjectivity. Sartre does not only suggest elements to understand body, consciousness and the world as a human and historical reality, but also elucidates how the subject, who is forged in intersubjectivity, constructs his/her personal and collective history.